Standard handbook of architectural engineering : a practical manual for architects, engineers, contractors and related professions and occupations - Butler, Robert Brown. (McGraw-Hill, 1998)
Introduction; design; Structure; Climate; Plumbing; Electrical; Illumination; Acoustics.